Electron density measurement from the emissivity ratio in hyperbolic geometry resampling the divertor of fusion reactor tokamak1 - Alhasi, Awad (Libyan Journal of Science &Technology, 2022)
Abstract The aim of this paper is to secure formula for measuring the electron density of the inhomogeneous plasma in divertor of the future reactor tokamaks such as the International Thermonuclear Experimental Reactor (ITER). This is done firstly by determining the emissivity ratio of the lines of hydrogen plasma to get the electron temperature. Secondly, we use the resulting temperature to infer the electron density. The emissivity ratio is obtained by hyperbolic inversion of the measured intensity of the lines. It is assumed that the free electrons have a Maxwellian velocity distribution and that the distribution of electron population over the bound levels is given by a coronal-type equation. The hydrogen plasma is assumed to be in a steady state without impurities contributing to the electron density